The Role of 5D Building Information Modelling in Construction Project Cost Management: An Overview and Future Directions - Mustafa, Muhammad Hadi; Mohd Rahim, Faizul Azli; Lee, Chia Kuang (Faculty Of Built Environment, University Of Malaya, 2023)
The significance of 5D BIM in construction project cost management is increasing as the construction industry has experienced significant technological advancements. Despite the growing importance of 5D BIM in construction project cost management, there is still a lack of comprehensive understanding regarding its full potential and the necessary skills and training required by professionals in utilizing this technology. Thus, there is a need to explore the benefits, challenges, and best practices of implementing 5D BIM in cost management, as well as the role of professionals in utilizing it for optimal results. This paper aims to address this knowledge gap through a systematic literature review and provide insights into the future of 5D BIM in construction project cost management. The paper discusses the benefits, challenges, and best practices of implementing 5D BIM in cost management. Furthermore, it examines the role of professionals in utilising 5D BIM for cost management, including the necessary skills, training, and team-building strategies. Additionally, the paper delves into the future of 5D BIM in cost management, exploring emerging trends and technological advancements. The conclusion summarises the key points and highlights the insights into future research directions